The chivalric folk tradition in Sicily : a history of storytelling, puppetry, painted carts and other arts - Croce, Marcella, 1949- (McFarland & Company, Inc., Publishers, 2014)
"Tracing the development in Sicily of a chivalric tradition based on the Medieval stories of Charlemagne and his knights, this analysis of Sicilian storytelling, puppetry, festivals, cart painting and other products of folk art offers a detailed portrait of an island unique in its geography and history"--